A Prospective Multicenter Clinical Observational Study on Vancomycin Efficiency and Safety With Therapeutic Drug Monitoring. (13th November 2018) - Liang, Xiaoyu; Fan, Yaxing; Yang, Minjie; Zhang, Jing; Wu, Jufang; Yu, Jicheng; Tao, Jinhao; Lu, Guoping; Zhang, Huifang; Wang, Ruilan; Wen, Xiaoxing; Li, Huayin; et al.
Abstract: Background: Vancomycin is a first-line antibiotic used for the treatment of severe gram-positive bacterial infections. Clinical guidelines recommend that the vancomycin trough concentration be 10–15 mg/L for regular infections and 15–20 mg/L for severe infections. We investigated whether increasing the vancomycin concentration would result in better clinical outcomes with sustainable adverse effects (AEs) in the Chinese population. Methods: A prospective, open, multicenter clinical observational study was performed in patients with gram-positive bacterial infections from 13 teaching hospitals. Patients received vancomycin therapeutic drug monitoring. Clinical, microbiological, and laboratory data were collected. Results: In total, 510 patients were enrolled, and 470 were evaluable, of whom 370 were adults and 100 were children; 35.53% had methicillin-resistant Staphylococcus aureus infections (vancomycin 50% minimum inhibitory concentration [MIC50 ] = 1, 90% minimum inhibitory concentration [MIC90 ] = 1), and 23.19% had Enterococcus species infections (vancomycin MIC50 = 1, MIC90 = 2). The average trough concentration was 10.54 ± 8.08 mg/L in adults and 6.74 ± 8.93 mg/L in children. The infection was eradicated in 86.22% of adults and 96% of children. Thirty-six vancomycin-related nephrotoxicity cases were reported in the enrolled population. No severe AEs or deaths were related to vancomycin therapy. Logistic regression analysis showed that trough concentration had no relationship with clinical outcomes (adults P = .75, children P = .68) but was correlated with adult nephrotoxicity ( P < .0001). Vancomycin trough concentration had an applicable cut point at 13 mg/L. Conclusions: Our study shows that vancomycin trough concentration has no statistical correlation with clinical outcomes, and is an indicator of nephrotoxicity in the observed population. We found no evidence that increasing vancomycin trough concentration to 15-20 mg/L can benefit Chinese patients with complicated infections. Clinical Trials Registration: ChiCTR-OPC-16007920.